Peribronchiolar Metaplasia: A Marker of Cigarette Smoke-Induced Small Airway Injury in a Rural Cohort - Rahul G Sangani; Vishal Deepak; Andrew J Ghio; Zalak Patel; Esra Alshaikhnassir; Jeffrey Vos (SAGE Publishing, 2023)
Background: Peribronchiolar metaplasia (PBM) is considered a reaction to injury characterized by the proliferation of bronchiolar epithelium into immediately adjacent alveolar walls. While an association of PBM with diffuse interstitial lung diseases has been recognized, the clinical significance of PBM remains uncertain. Methods: A cohort (n = 352) undergoing surgical resection of a lung nodule/mass in a rural area was retrospectively reviewed. Multivariate logistic regression analysis was performed to determine the association of PBM with clinical, physiological, radiographic, and histologic endpoints. Results: In the total study cohort, 9.1% were observed to have PBM as a histologic finding in resected lung tissue (n = 32). All but one of these patients with PBM were ever-smokers with a median of 42 pack years. Clinical COPD was diagnosed in two-thirds of patients with PBM. Comorbid gastroesophageal reflux disease (GERD) was significantly associated with PBM. All patients with PBM demonstrated radiologic and histologic evidence of emphysema. Measures of pulmonary function were not impacted by PBM. Mortality was not associated with the histologic observation of PBM. In a logistic regression model, centrilobular-ground glass opacity interstitial lung abnormality and traction bronchiectasis on the CT scan of the chest and histologic evidence of fibrosis, desquamative interstitial pneumonia and anthracosis all strongly predicted PBM in the cohort. Conclusion: A constellation of radiologic and histologic smoking-related abnormalities predicted PBM in study cohort. This confirms a co-existence of lung tissue responses to smoking including PBM, emphysema, and fibrosis. Acknowledging the physiologically "silent" nature of small airway dysfunction on pulmonary function testing, our findings support PBM as a histologic marker of small-airway injury associated with cigarette smoking.